Pemanfaatan TikTok Sebagai Media Promosi PPDB SMK Mahadhika 4 Jakarta Timur Pada Tahun Ajaran 2023/2024 - Arif Krisbiantoro; Akhmad Syafrudin Syahri (CV. ITTC INDONESIA, 2024)
In the modern era, communication media have become completely digital and now a new term is starting to emerge, namely New Media. This is also due to the increasingly massive use of the internet in various countries, one of which is Indonesia. One form of communication is promotional activities which aim to inform about goods or services. The aim of this research was to see how SMK Mahadhika 4 Jakarta utilizes one of the New Media, namely TikTok, as a means of their promotion in the PPDB (New Student Acceptance) program by looking at the content presented by the smkmahadhika4 account on their TikTok media. The research method used in this thesis uses descriptive qualitative methods with the Miles, Huberman and Saldana data processing model. This research seeks to collect data from observations, documentation and interviews related to the use of New Media, namely TikTok as a means of promoting SMK Mahadhika 4 Jakarta in the PPDB (New Student Acceptance). The author draws the conclusion that in using TikTok as a promotional tool for PPDB SMK Mahadhika 4 Jakarta, TikTok is used as a medium to convey information with various types of content such as entertainment, music, animation and other informative content, but the use of TikTok media has not had a direct impact on PPDB SMK Mahadhika 4 Jakarta.